Workplace violence against healthcare workers during the COVID‐19 pandemic in Sudan: A cross‐sectional study. Issue 4 (2nd November 2022) - Elhadi, Yasir Ahmed Mohammed; Mohamed, Hammad Mohamed Hammad; Ahmed, Abdelmuniem; Haroun, Islam Hamza; Hag, Mohamed Hassan; Farouk, Ehssan; Almadani, Moaaz; Mohamed, Alanood Elnaeem; Adam, Mohammed Fathelrahman; Abdelhamed, Osman S.; Salih, Elhadi Basheer; Mohamed, Sahar Khalid; et al.
Abstract: Background: Workplace violence (WPV) against healthcare workers (HCWs) is a growing global issue. During the coronavirus diseases‐2019 (COVID‐19) pandemic, violent attacks on HCWs have been documented worldwide. This study aimed to investigate the magnitude and pattern of WPV among HCWs in Sudan during the COVID‐19 pandemic. Methods: A web‐based cross‐sectional study of WPV was conducted among registered medical and health workers (pharmacists, physicians, dentists, nurses, laboratory technicians, and administrative and paramedical staff) during the COVID‐19 pandemic in Sudan. Data were collected from August to December 2021 using a self‐administered questionnaire distributed through social media platforms. Results: A total of 792 HCWs returned the online questionnaire. The mean age was 33.5 ± 8.6 years, where more than half were females (54.9%) and working during the day shift (58.8%). During the COVID‐19 pandemic, three out of every four participants (78.3%) reported experiencing violence, with 65.8 % experiencing it more than three times. The common types of violence experienced were verbal (91.6%), physical (50.0%), and sexual abuse (11.0%). The emergency department reported the highest number of violent incidents (46.9%). Half of these violent events were not reported (50.3%), primarily due to a lack of a reporting system. The demographic factors that were significantly associated with exposure to violence were participants' occupation ( p  < 0.001), age ( p  = 0.001), marital status ( p  = 0.002), and years of working experience ( p  = 0.020). Conclusion: WPV was rampant among the HCWs in Sudan during the COVID‐19 pandemic. The current findings are presented to draw the attention of policy leaders and stakeholders in Sudan to this alarming problem prompting the pressing need for policy and system interventions.